Combined Superior Mesenteric Artery Syndrome and Nutcracker Syndrome in a Young Male Patient Presenting as Atypical Vomiting and Rapid Weight Loss: A Case Report - Dahir Alasow MO; Elmi AM; Haji AM; Jama SMA; Hirei HH; Osman AA (International Medical Case Reports Journal)
Mohamed Osman Dahir Alasow, Abdinasir Mohamed Elmi, Abdirahman Mahmud Haji, Shuayb Moallim Ali Jama, Hanan Hassan Hirei, Ahmed Adam Osman Radiology Department, Mogadishu Somali Turkey, Recep Tayyip Erdogan Training and Research Hospital, Mogadishu, SomaliaCorrespondence: Mohamed Osman Dahir Alasow, Radiology Department, Mogadishu Somali Turkey, Recep Tayyip Erdogan Training and Research Hospital, 30 Street, Albarako, Hodan District, Mogadishu, Somalia, Tel +252615428952, Email mcalasow00@gmail.comAbstract: Superior mesenteric artery (SMA) syndrome, also known as Wilkie syndrome, is an uncommon condition marked by the compression of the third segment of the duodenum between the SMA and the aorta, often occurring after rapid weight loss, particularly in young, slim individuals. Symptoms consist of epigastric pain, bloating, and vomiting. Nutcracker syndrome (NCS) is characterized by the compression of the left renal vein (LRV) between the superior mesenteric artery and the aorta. This condition results in venous varices and elevated pressure within the LRV, which may manifest as hematuria, proteinuria, pelvic congestion, and flank pain. Although each of these syndromes is infrequent, their simultaneous incidence is remarkably occasional. This case report examines a young male patient diagnosed with both SMA syndrome and NCS, emphasizing the importance of considering these conditions in the differential diagnosis of abdominal and renal symptoms.Keywords: superior mesenteric artery syndrome, nutcracker syndrome, left renal vein, vomiting, duodenal obstruction